First record of anaxyelid woodwasps (Hymenoptera: Anaxyelidae) in Lower Cretaceous Spanish amber - Ortega-Blanco, J.; Rasnitsyn, A. P.; Delclòs, X. (Zootaxa, 2008)
A new species of the family Anaxyelidae (Eosyntexis parva n. sp.) is described. This is the first record of the family from Lower Cretaceous Spanish amber. The specimen is mostly well preserved, except for dorsally. This makes it possible to identify several important details rarely or never observed in compression fossils. Eosyntexis spp. and the closely related genus Cretosyntexis are confined to the Eurasian Lower Cretaceous, whereas the extant monotypic genus Syntexis is restricted to western North America. The morphology of this new species suggests xylophagous habitus, and its relation with Syntexis libocedrii implies a possible relationship with burned wood, apparently a frequently available resource in northern Spanish forests of the Lower Cretaceous.